Barriers to COVID-19 vaccine uptake: classification and the role of Health Literacy and Media Literacy - Ranjbaran, Soheila; Chollou, Khalil Maleki; Pourrazavi, Sara; Babazadeh, Towhid (Frontiers in Public Health, 2023)
Background Vaccination is one of the most influential and cost-effective health interventions for preventing and reducing COVID-19 diseases. Unfortunately, the majority of the world's population is deprived of vaccination. Health Literacy (HL) and Media Literacy (ML) are essential to the COVID-19 vaccination. The present study investigates the barriers to COVID-19 vaccine uptake, focusing on classification and the roles of HL and ML. Methods A cross-sectional study was conducted among people 18–65 years old in Sarab City, located in East Azerbaijan, Iran, between September to October 2020. Multistage cluster sampling was employed to recruit 298 people from Health Care Services Centers (HCCs). Results The results of this research demonstrated that about 32.6% of participants reported that they have fully injected COVID-19 vaccines. Also, HL was positively associated with ML (r = 0.214, p < 0.05). Barriers of COVID-19 vaccine uptake were classified into personal, interpersonal, group and organizational, society and decision-making factors. Besides, barriers to the COVID-19 vaccine were significantly correlated with HL (r = −0.298, p < 0.05) and ML (r = 0.266, p < 0.05). Additionally, in the hierarchical regression model, demographic characteristics accounted for 8.2% of the variation in barriers to the COVID-19 vaccine (F = 4.34; p = 0.001), that monthly income (ß = −0.237; p < 0.05) and marriage statues (ß = 0.131; p < 0.05) were statistically associated with low barriers. HL as predictor variables explained an additional 14.4% of variation in barriers of COVID-19 vaccine (F = 53.84; p < 0.001) and ML explained an extra 9.2% of the variation (F = 38.83; p < 0.001). In total, demographic characteristics, HL dimensions and ML were able to explain 31.8% of the variation in barriers to COVID-19 vaccine. Conclusions According to the findings, various strategies are needed to increase the COVID-19 vaccination uptake. This is due to the fact that barriers to COVID-19 vaccination uptake are multifactorial. These facts can help health policymakers and healthcare providers design media-based interventions to reduce barriers to COVID-19 vaccination uptake among adults. Enhancing vaccine HL and ML for adults and improving vaccine confidence are of high priority.